'It's like it doesn't really matter': Are teachers accountable and equipped for teaching primary physical education?. Issue 2 (17th February 2022) - Mcveagh, Hollie; Smith, Matt; Randall, Victoria
ABSTRACT: In light of the recent trend of outsourcing Physical Education teaching, the aim of this study was to examine primary teachers' perspectives of primary Physical Education delivery. Fourteen in-service primary school teachers took part in semi-structured interviews. Thematic analysis led to the development of six themes. Findings were presented as a written playscript, representing dialogue between group primary school teachers, with reflections of four Physical Education subject leads included to supplement the dialogue. The findings suggest a greater emphasis on accountability, subject advocacy, teacher professional development and effective deployment of resources are needed to address the issues raised by the primary teachers.